Effects of Work–Family Conflict on Southern Correctional Staff Burnout. (January 2022) - Lambert, Eric G.; Keena, Linda D.; Morrow, Weston J.; Vickovic, Samuel G.; Haynes, Stacy H.; May, David; Leone, Matthew C.
Research examining correctional staff indicates that there are far-reaching negative consequences related to job burnout, including, but not limited to, diminished physical and mental health, increased risk of substance use, and decreased job performance. One area that may contribute to correctional staff job burnout is work–family conflict, which occurs when work and home domains spill into one another, causing conflict and problems. Using a sample of Southern correctional staff, this study investigates whether the four major types of work–family conflict—time-based, strain-based, behavior-based, and family-based—influence the three recognized job burnout dimensions: emotional exhaustion, depersonalization, and feeling ineffective at work. The findings provide partial support for the notion that work–family conflict influences job burnout. These findings are contextualized in previous research with a full discussion of their implications.